2020
DOI: 10.1038/s41598-020-69064-1
|View full text |Cite
|
Sign up to set email alerts
|

Specific localisation of ions in bacterial membranes unravels physical mechanism of effective bacteria killing by sanitiser

Abstract: Antimicrobial resistance is a major threat to public health. Although many commercial sanitisers contain a combination of cationic surfactants and aromatic alcohols, the physical mechanisms where these two substances bind to or how they disturb bacterial membranes are still largely unknown. In this study, we designed a well-defined model of Gram-negative bacteria surfaces based on the monolayer of lipopolysaccharides with uniform saccharide head groups. Since commonly used X-ray reflectivity is sensitive to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 32 publications
(50 reference statements)
4
13
1
Order By: Relevance
“…Different cations are known to elicit unique morphological properties in LPS monolayers and bilayers. Coughlin et al reported that purified sodium LPS salt forms tube-like aggregates, while the presence of divalent cations calcium or magnesium induces the formation of LPS bilayer aggregates. , Many studies have also noted that the high activity of divalent cations leads to the displacement of monovalent cations weakly bound to the saccharide headgroups, with calcium binding more tightly relative to magnesium. , The striking sensitivity of LPS aggregate morphology to cation type, and the high preference for calcium binding, has also been associated with the resistance of bacteria to commercial sanitizers; calcium is suggested to cross-link the saccharide chains together, preventing membrane penetration by the weaker cationic surfactants used in sanitizers . A similar mechanism may play a role in the reactive uptake of trace atmospheric gases by marine aerosols, but the specific impacts of cation type on LPS-transformed SSA particle morphology and reactivity remain unclear.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Different cations are known to elicit unique morphological properties in LPS monolayers and bilayers. Coughlin et al reported that purified sodium LPS salt forms tube-like aggregates, while the presence of divalent cations calcium or magnesium induces the formation of LPS bilayer aggregates. , Many studies have also noted that the high activity of divalent cations leads to the displacement of monovalent cations weakly bound to the saccharide headgroups, with calcium binding more tightly relative to magnesium. , The striking sensitivity of LPS aggregate morphology to cation type, and the high preference for calcium binding, has also been associated with the resistance of bacteria to commercial sanitizers; calcium is suggested to cross-link the saccharide chains together, preventing membrane penetration by the weaker cationic surfactants used in sanitizers . A similar mechanism may play a role in the reactive uptake of trace atmospheric gases by marine aerosols, but the specific impacts of cation type on LPS-transformed SSA particle morphology and reactivity remain unclear.…”
mentioning
confidence: 99%
“…One possible explanation for the cation-dependent differences in morphology and reactivity of LPS bilayers is that divalent cations, by chelating two singly charged reactive sites each, deform the structures of the oligosaccharides while positioning them into ideal cross-linking conformations, which simultaneously dehydrates the O-antigen regions and blocks the movement of water. ,,,, Monovalent sodium cations do not appear to significantly disrupt the alignment of the LPS molecules; however, divalent cations induce structural deformation away from the bilayer normal in the oligosaccharide chains, which increases the molecular footprint of each LPS molecule and causes the bilayer to expand. Notably, the increase in area per molecule does not correspond to an increase in water diffusion throughout aggregate; rather, the LPS conformations hinder water diffusion by forming a relatively dehydrated and intertwined network of saccharide chains, also known as microgels, which have been observed in marine environments .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These Langmuir monolayer models have been extensively used to explore the interaction of antimicrobial agents with the bacterial membrane. For example, a monolayer of Ra-LPS from a Salmonella enterica rough mutant, resembling a Gram-negative bacterial outer membrane, was spread over the interface of the Langmuir film balance to understand the influence of aromatic alcohol and cationic surfactants on bacterial outer membrane structures [ 68 ].…”
Section: Formation Of Various Bacterial Model Membranesmentioning
confidence: 99%
“…However, all bacteria exposed to the BAC and BzA mixture died within 3 min, which clearly indicates that the two ingredients act synergistically. Recent XRR/GIXF data demonstrated that BAC (5 μM) binds to the negatively charged saccharide head group and penetrated the hydrophobic membrane core in the absence but not in the presence of Ca 2+ ions . However, once a nonlethal concentration of BzA (100 mM) was added, the chain/saccharide interface became rougher, allowing BAC to overcome the electrostatic barrier and disrupt the LPS membrane.…”
Section: Introductionmentioning
confidence: 99%